PERTIMBANGAN HAKIM DALAM PENYELESAIAN SENGKETA KEPAILITAN (ANALISIS PUTUSAN NOMOR 08/PDT.SUS-PAILIT/2024/PN. NIAGA SMG) - Wira OktaViana; Iyah Faniyah; Nabila Putri Syarifa Asan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract: Bankruptcy is regulated under Article 1 of Law Number 37 of 2004 concerning Bankruptcy and Suspension of Debt Payment Obligations, which states that bankruptcy is a general seizure of all assets of a bankrupt debtor, the management and settlement of which are carried out by a receiver under the supervision of a supervisory judge as provided in this law. Bankruptcy experienced by a company is caused by financial losses and excessive debt, leading the debtor to file a petition, as occurred with PT. Arga Dumilah, which had been liquidated in Decision Number 08/Pdt.Sus-Pailit/2024/PN Niaga Smg. The research problems addressed in this study are as follows: First, how was the judge's consideration in resolving the bankruptcy dispute in Decision Number 08/Pdt.Sus-Pailit/2024/PN Niaga Smg? Second, what are the legal consequences of the judicial decision Number 08/Pdt.Sus-Pailit/2024/PN Niaga Smg on the bankruptcy dispute of PT. Arga Dumilah? This research is descriptive in nature. The approach method used is normative juridical by conducting an in-concreto legal study, specifically examining law in the form of judicial decisions. The data sources used are secondary data consisting of primary, secondary, and tertiary legal materials. Data collection techniques in this study were conducted through library research or legal document studies. All collected data were analyzed qualitatively and presented in a descriptive qualitative format. Based on the research findings and discussion, the author concludes as follows: First, regarding the judge's consideration in resolving the bankruptcy dispute in Decision Number 08/Pdt.Sus-Pailit/2024/PN Niaga Smg, the judge not only considered the fulfillment of formal elements of bankruptcy—namely the presence of more than one creditor and due and payable debt—but also evaluated the material elements of the company, taking into account the actual condition of the company which had entered the liquidation stage and no longer possessed adequate assets to fulfill its obligations to its creditors. Second, the legal consequences of the judicial decision in the bankruptcy dispute in Decision Number 08/Pdt.Sus-Pailit/2024/PN Niaga Smg dictate that upon the pronouncement of the bankruptcy declaration, the company legally acquired the status of a bankrupt debtor as regulated under Law Number 37 of 2004. This status causes all company assets, both those owned at the time the decision was rendered and those acquired during the bankruptcy process, to become part of the bankruptcy estate (boedel pailit) placed under general attachment for the benefit of all creditors. Consequently, the company loses its authority to control or manage its own assets, as such authority transfers to the receiver (curator) who performs duties under the supervision of the supervisory judge in accordance with statutory regulations. Keywords: Judicial Consideration, Dispute, Bankruptcy.